In the Digital Age, Collaboration is the First Step Toward Unlocking Innovation in the Workplace - Matius Kalatiku (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Collaborative innovation has become crucial for organizations that wish to stay relevant and competitive in the quickly evolving digital age. There are plenty of opportunities, but there are also several obstacles to overcome. Information and data security in a digital world vulnerable to cyberattacks is one of the biggest problems. Sophisticated security measures must be implemented by organizations to safeguard confidential data that is shared among team members. Resistance to change is also an obstacle that needs to be overcome. When organizations adopt new technology, employees often face difficulties adapting. Organisations can create more efficient and effective solutions with the latest technologies, such as artificial intelligence and data analysis. Collaboration across industries and disciplines enables a holistic approach to solving complex problems. By understanding and overcoming existing challenges, organizations can harness the potential of collaborative innovation in the digital era to create added value, increase efficiency, and ensure business continuity in an ever-changing world.